Diseño de un biodigestor automatizado para la granja Zapotepamba de la Universidad Nacional de Loja. - Díaz Castillo, Darío Alexander (2011)
The Automatic Biodigestor design is aimed to solving the problems that crosses the farm Zapotepamba in the National University of Loja in regard to the high demand for liquefied gas for cooking food, in addition to resolving the treatment of animal manure with fertilizer to obtain higher quality in less time. To develop the research process we use the traditional method of observation and interview, we took into consideration the experience of teachers and students from the farm for the realization of a draft that gave us the guidelines for the development of our research project. The main objective of this work is to design and simulated a biodigester with traditional storage tank and polyethylene dome semi-flow horizontal displacement. Which will allow for the automation processes all involved in procurement and production of manure to more than the collection of biogas for cooking and heating in an automated incubator, as a result of anaerobic descomposition of plant litter and animal manure waste. This work of research is performed with the desire to contribute to environment, with the help of the engineering and automatic processes in the firm conviction to contribute to the conservation of our natural environment with the use of alternative energies. By this model succeed in building a biogas generation plant and biofertilizer in small spaces with greater performance against other.